Mechanical form-Finding of the Timber Fabric Structures with Dynamic Relaxation Method. Issue 3 (September 2013) - Nabaei, Seyed Sina; Baverel, Olivier; Weinand, Yves
Timber Fabric structures (TFS) initiate from a correspondence between textile principles and recent industrial developments in producing cross laminated timber panels. Several individual timber strips are interlaced according to a pattern and result in an innovative space structure. The obtained three-dimensional geometry can be regarded as the relaxed configuration of deformed panels under the imposed boundary conditions. We herein propose a form-finding procedure, which reproduces this deformed configuration as the steady state of a pseudo transient constrained dynamic problem. The corresponding nonlinear problem involves finite rotation regime and contact handling through the cross section and on both panel faces. To effectively deal with nonlinear constraints, a new modified dynamic relaxation method is herein used which combines elastic material behavior with a fictitious stiffness proportional damping into an equivalent fictitious viscous material model. The procedure is implemented as an ABAQUS/Explicit user subroutine VUMAT and the overall accuracy of the numerical results has been studied for a number of geometrically nonlinear shell benchmark problems. This numerical approach is then employed to simulate the assembly process for a Timber Fabric Module (TFM), an interlaced assembly of two timber strips. The simulated geometry for the deformed surfaces is then extracted and is compared with a 3D processed surface mesh obtained from scanning a built-in prototype with noncontact Laser scanner arm to validate the simulation procedure.